ChemInform Abstract: Solvent‐ and Ligand‐Free Diboration of Alkynes and Alkenes Catalyzed by Platinum Nanoparticles on Titania. Issue 33 (19th August 2014) - Alonso, Francisco; Moglie, Yanina; Pastor‐Perez, Laura; Sepulveda‐Escribano, Antonio
Abstract Pt/TiO2‐catalyzed diborations of terminal and internal alkynes (I, IV and VI) as well as cyclic alkenes (XII) run in a stereoselective manner (cis‐diboration).